A study on the morphology of natural microfractures in marine and continental transitional shale based on scanning electron microscopy image. (September 2021) - Wei, Xiaoliang; Zhang, Yuxing; Zhang, Shun; Zhang, Jinchuan; Shi, Miao
Highlights: For the first time, image evidence of microfractures in shale generate in the surface environment is provided. Describes the characteristics of natural underground shale microfractures and microfractures induced in surface environment. Summarized the conditions for natural shale microfractures to remain open underground. Abstract: The development of natural microfractures not only directly affects exploitation efficiency of a shale gas reservoir, but also determines the quality and production of the shale gas reservoir. The environment, in which the shale forms, is considered to be the fundamental cause of shale pore formation and deformation. However, the traditional method of observing shale samples using field-emission scanning electron microscopy (FE-SEM) can be interfered by a large number of fractures caused by artificial damage on the shale surface during sample preparation, such as mechanical damage during polishing and shrinkage damage of shale mineral particles. To tackle this issue, we summarized the features of natural fractures by comparing fracture morphology of shale before and after artificial damage. In this study, the powder samples which suffered serious structural damage and the block samples with light structural damage were observed by FE-SEM. In addition, we used the pressure switch to cause slight damage to the surface of gold-plated block samples, and the difference between the gold film tearing edge and the mineral tearing edge was used to identify the artificial cracks generated during this process. We found (1) most of the open structural fractures on the shale surface are not natural, but artificially induced during the sample preparation process; (2) most non-structural natural fractures are mainly related to organic matter, clay and calcite; (3) stress and shrinkage are the main causes of natural microfractures; (4) natural microfractures in shale have a clear pressure support structure, which are categorized into self-supporting fractures.